Politik Hukum dalam Penanganan Konflik Agraria di Indonesia - Setia Budi, Fatkur Rochman (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study is to explain how legal politics plays a role in resolving agrarian conflicts and what are the political obstacles that interfere with the effectiveness of resolving agrarian conflicts in Indonesia. The research method used is normative-juridical, which emphasizes the study of legal principles and legal synchronization. The results of the study indicate that the resolution of agrarian conflicts refers to the Basic Agrarian Law (UUPA) of 1960 which is the main legal basis, but its implementation is often hampered by various conflicting political and economic interests, one important aspect of legal politics is the ability to accommodate the rights of local communities There are several obstacles, namely the influence of corruption and abuse of power in land control, lack of strict supervision that harms weak parties, and lack of government involvement in creating policies that support the resolution of agrarian conflicts.